2014
DOI: 10.1002/pon.3554
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of patient-reported neurobehavioral problems following hematopoietic stem cell transplant and health-related quality of life

Abstract: Findings from this preliminary study highlight the importance of investigating neurobehavioral problems, particularly apathy, in HSCT patients. Because apathy is often confused with other diagnoses and may worsen HRQOL, understanding the nature of these symptoms has implications for interventions. Further research is needed in this important area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Only recently has the existence of such symptoms been reported in cancer patients by our team (Wu et al, 2014). In the present study, the neurobehavioral symptoms of emotional lability and impulsivity (both aspects of disinhibition) were reported by significantly more ADT than nADT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has the existence of such symptoms been reported in cancer patients by our team (Wu et al, 2014). In the present study, the neurobehavioral symptoms of emotional lability and impulsivity (both aspects of disinhibition) were reported by significantly more ADT than nADT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some neurobehavioral problems, particularly apathy, were observed in patients after HCT. 33 Although cognitive impairments are evident for a subset of patients before HCT, results from a meta-analysis suggest that cognition does not significantly change after HCT. 34 What Is the Impact of Cancer on Cognition?…”
Section: Report From the 2012 Icctf Paris Meetingmentioning
confidence: 99%
“…Our study revealed that the participants' experiences of both cognitive impairment and especially the endless sense of fatigue played a major role for NMA‐HSCT patients because these experiences influence and challenge the entire process of adapting to changes. Other studies have found that below average cognitive performance is common after allogeneic stem cell transplant (Scherwath et al, ; Wu et al, ). The extent and severity of the problem have, however, not been clarified (Harder et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…The extent and severity of the problem have, however, not been clarified (Harder et al, ; Wu et al, ). Subjective cognitive impairment reduces HSCT patients’ confidence in their ability to manage common post‐transplant symptoms (Wu et al, ) and health‐related quality of life (Wu et al, ). Patients who report cognitive impairment are likely to benefit from interventions that enhance their confidence in the management of emotional symptoms (Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%